The Neoliberal Racial Project: The Tiger Mother and Governmentality. Issue 6 (December 2013) - Rhee, Jeong‐eun
Abstract Combining the conceptual approach of racial formation and racial projects with the Foucauldian concept of governmentality, Jeong‐eun Rhee theorizes the "neoliberal racial project" (NRP) and examines contemporary meanings and operations of race and racism in relation to neoliberalism. She analyzes Amy Chua's popular parenting memoir, Battle Hymn of the Tiger Mother, as a specific case of the NRP, and demonstrates how in this text race is pressed to work in new — neoliberal — ways, re/generating different kinds of categories and meanings, yet also continuously drawing upon old categories and meanings, to effect and rationalize social arrangements of power and exploitation, violence and expropriation. What is noteworthy is the way in which racial neoliberalism builds silently on the structural conditions of racism while disabling the very categories of their recognizability. Consequently, Rhee argues for new, historically bounded theories that can articulate how the meanings, categories, and concepts of races are constantly being reconfigured.